Nocturnal Southerly Moist Surge Parallel to the Coastline Over the Western Bay of Bengal - Hatsuki Fujinami; Tomonori Sato; Hironari Kanamori; Masaya Kato (Geophysical Research Letters, 2022)
Abstract The role of the diurnal atmospheric circulation cycle around the eastern Indian subcontinent, leeward of the monsoon westerlies, on the hydroclimate of South Asia remains unknown. Here, we reveal that low‐level moist southerlies are greatly enhanced at night parallel to the coastline over the western Bay of Bengal (BoB), and then flow onto the Gangetic Plain enhancing onshore moisture flux and nocturnal precipitation over the Himalayas and the Meghalaya Plateau. This nocturnal surge is strongly controlled by the diurnal cycle of dynamic and thermodynamic effects around the subcontinent. At night, nocturnal westerly low‐level jets appear over the subcontinent. Strong low‐level southwesterly flow with a low‐level jet structure also appears parallel to the coastline over the western BoB, extending from the west of Sri Lanka. The low‐level westerlies from the subcontinent and the low‐level southwesterlies merge into a single strong southwesterly flow, forming the low‐level moist surge.